Empowering Families with DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) : Promoting Safe and Responsible Medicine Management in The Teluk Sanggar Community, Banjar Regency, South Kalimantan - Pribadi, Anjar; Norsyipa, Norsyipa; Putri, Arvina Rafika; Salman, Yuliana; Zaini, Muhammad; Husin, Husin (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aimed to enhance public understanding of the DAGUSIBU concept (Dapatkan, Gunakan, Simpan, Buang) as part of an educational effort to promote safe and responsible medication management within the family environment. The methods employed included Focus Group Discussions (FGD) and counseling, with evaluations carried out through pretest and posttest assessments to measure changes in participants' knowledge. The program involved 32 residents of Teluk Sanggar Village, Martapura District, Banjar Regency, with 53.13% male and 46.87% female participants. The evaluation results indicated a significant increase in participants' knowledge after the intervention. The percentage of participants in the